Phage-mediated virulence loss and antimicrobial susceptibility in carbapenem-resistant Klebsiella pneumoniae - Yanshuang Yu; Mengzhu Wang; Liuying Ju; Minchun Li; Mengshi Zhao; Hui Deng; Christopher Rensing; Qiu E. Yang; Shungui Zhou (mBio)
ABSTRACT Bacteriophages, known for their ability to kill bacteria, are hampered in their effectiveness because bacteria are able to rapidly develop resistance, thereby posing a significant challenge for the efficacy of phage therapy. The impact of evolutionary trajectories on the long-term success of phage therapy remains largely unclear. Herein, we conducted evolutionary experiments, genomic analysis, and CRISPR-mediated gene editing, to illustrate the evolutionary trajectory occurring between phages and their hosts. Our results illustrate the ongoing “arms race” between a lytic phage and its host, a carbapenem-resistant Klebsiella pneumoniae clinical strain Kp2092, suggesting their respective evolutionary adaptations that shape the efficacy of phage therapy. Specifically, Kp2092 rapidly developed resistance to phages through mutations in a key phage receptor (galU) and bacterial membrane defenses such as LPS synthesis, however, this evolution coincides with unexpected benefits. Evolved bacterial clones not only exhibited increased sensitivity to clinically important antibiotics but also displayed a loss of virulence in an in-vivo model. In contrast, phages evolved under the selection pressure against Kp2092 mutants and exhibited enhanced bacterial killing potency, targeting mutations in phage tail proteins gp12 and gp17. These parallel evolutionary trajectories suggest a common genetic mechanism driving adaptation, ultimately favoring the efficacy of phage therapy. Overall, our findings highlight the potential of phages not only as agents for combating bacterial resistance, but also a driver of evolution outcomes that could lead to more favorable clinical outcomes in the treatment of multidrug resistance pathogens.IMPORTANCECarbapenem-resistant Klebsiella pneumoniae represents one of the leading pathogens for infectious diseases. With traditional antibiotics often being ineffective, phage therapy has emerged as a promising alternative. However, phage predation imposes a strong evolutionary pressure on the rapid evolution of bacteria, challenging treatment efficacy. Our findings illustrate how co-evolution enhances phage lytic capabilities through accumulated mutations in the tail proteins gp12 and gp17, while simultaneously reducing bacterial virulence and antibiotic resistance. These insights advance our understanding of phage-host interactions in clinical settings, potentially inspiring new approaches akin to an “arms race” model to combat multidrug-resistant crises effectively.